Oropetium almeidanum (Poaceae: Chloridoideae): a new species from The Thar Desert, Rajasthan, India - Shinde, Rajendra D.; Landge, Shahid Nawaz; Kulloli, R.n.; Chorghe, Alok R. (Phytotaxa, 2023)
Oropetium almeidanum, a new species has been described from Thar Desert, Jaisalmer, Rajasthan based on the specimens collected recently from Jaisalmer and a specimen present in the Blatter Herbarium (BLAT). The new grass is allied to three African species viz.,O. minimum, O. capense and O. aristatum. Detailed description, photo plate and illustration of a new species along with a brief discussion on its close affinities are given. Key to distinguish all the species of Oropetium in the world along with the table of their detailed morphological comparison is provided to facilitate their proper identification.